Charge and lipophilicity are required for effective block of the hair-cell mechano-electrical transducer channel by FM1-43 and its derivatives - Derudas, Marco; O’Reilly, Molly; Kirkwood, Nerissa K.; Kenyon, Emma J.; Grimsey, Sybil; Kitcher, Siân R.; Workman, Shawna; Bull, James C.; Ward, Simon E.; Kros, Corné J.; Richardson, Guy P. (Frontiers in Cell and Developmental Biology, 2023)
The styryl dye FM1-43 is widely used to study endocytosis but behaves as a permeant blocker of the mechano-electrical transducer (MET) channel in sensory hair cells, loading rapidly and specifically into the cytoplasm of hair cells in a MET channel-dependent manner. Patch clamp recordings of mouse outer hair cells (OHCs) were used to determine how a series of structural modifications of FM1-43 affect MET channel block. Fluorescence microscopy was used to assess how the modifications influence hair-cell loading in mouse cochlear cultures and zebrafish neuromasts. Cochlear cultures were also used to evaluate otoprotective potential of the modified FM1-43 derivatives. Structure-activity relationships reveal that the lipophilic tail and the cationic head group of FM1-43 are both required for MET channel block in mouse cochlear OHCs; neither moiety alone is sufficient. The extent of MET channel block is augmented by increasing the lipophilicity/bulkiness of the tail, by reducing the number of positive charges in the head group from two to one, or by increasing the distance between the two charged head groups. Loading assays with zebrafish neuromasts and mouse cochlear cultures are broadly in accordance with these observations but reveal a loss of hair-cell specific labelling with increasing lipophilicity. Although FM1-43 and many of its derivatives are generally cytotoxic when tested on cochlear cultures in the presence of an equimolar concentration of the ototoxic antibiotic gentamicin (5 µM), at a 10-fold lower concentration (0.5 µM), two of the derivatives protect OHCs from cell death caused by 48 h-exposure to 5 µM gentamicin.